« Ô ma Muse, prends la Mercedes, mets le contact et démarre ! ». Note sur les vecteurs de la parole dans quelques poèmes tribaux yéménites contemporains - Julien Dufour; Hanan Maloom (Arabian Humanities)
Of all the poetic genres that are cultural practices in tribal Yemen, the qaṣīda is the closest thing to a fixed text, distinct from the moment of enunciation. Furthermore, the stereotyped structure of the qaṣīda involves formulaic borrowing from Classical Arabic (religious supplications at the opening and end of the poem), as well as a messenger motif, one meant to deliver the text of the message to its recipient. This has led some to hypothesize that the genre of the qaṣīda with its characteristic structure appeared in answer to the epistolary needs of literate poets living in an oral environment.Through the analysis of four contemporary Yemeni poems, this article puts the question the other way and aims to show that it is in the very nature of the qaṣīda to stage the time between sending and receiving the message, as well as the resulting mediation between those involved in the matter at hand. Thus, references to writing or to messengers with which writers punctuate their texts may be put down to the demands of the genre, which would also explain why the radio, television and various means of transportation are also mentioned.